Food fibers in metabolic syndrome and non-alcoholic fatty liver disease - E. V. Onuchina (Лечащий Врач)
Modern awareness of the role of food fibers in the management of metabolic syndrome as a whole, and of non-alcoholic fatty liver disease in particular was presented, basing on the data from the most modern foreign literature.